2019
DOI: 10.1111/bioe.12590
|View full text |Cite
|
Sign up to set email alerts
|

How palliative care patients’ feelings of being a burden to others can motivate a wish to die. Moral challenges in clinics and families

Abstract: The article explores the underlying reasons for patients’ self‐perception of being a burden ( SPB ) in family settings, including its impact on relationships when wishes to die ( WTD ) are expressed. In a prospective, interview‐based study of WTD in patients with advanced cancer and non‐cancer disease (organ failure, degenerative neurological disease, and frailty) SPB was an important emerging theme. In a sub‐analysis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 0 publications
1
39
0
3
Order By: Relevance
“…In addition, it seems possible that patients with SPMI might benefit from a palliative care approach ( 4 ). In cases of perceived burdensomeness, this issue must be addressed in the therapeutic process to alleviate that element of suffering ( 28 , 32 , 34 , 35 , 37 ), not least because patients have indicated that it is difficult to talk about this with their family ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, it seems possible that patients with SPMI might benefit from a palliative care approach ( 4 ). In cases of perceived burdensomeness, this issue must be addressed in the therapeutic process to alleviate that element of suffering ( 28 , 32 , 34 , 35 , 37 ), not least because patients have indicated that it is difficult to talk about this with their family ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is also a risk that relatives may unconsciously or unintentionally pressure the patient to seek MAID ( 17 ) and that their opinion may play an important role in any such decision, regardless of whether the patient has a mental illness ( 9 , 15 , 38 ). For example, a patient might reject MAID because their family is against this approach ( 17 , 34 ). In one study of family members of patients who lacked decision-making capacity (DMC), Winter and Parks ( 44 ) found that when there was any disagreement, family members tended to favor life-prolonging rather than palliative care approaches and that the decision was influenced more by family members than by the patient's own preference.…”
Section: Should Perceived Burdensomeness Be a Reason For Refusing Maimentioning
confidence: 99%
See 3 more Smart Citations